2020
DOI: 10.21203/rs.3.rs-46092/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Vagal Afferent Fibers Contribute to the Anti-Inflammatory Reactions by Vagus Nerve Stimulation in Concanavalin A Model of Hepatitis in Rats

Abstract: Background: Increasing number of studies provide evidence that the vagus nerve stimulation (VNS) dampens inflammation in peripheral visceral organs. However, the effects of afferent fibers of the vagus nerve (AFVN) on anti-inflammation have not been clearly defined. Here, we investigate whether AFVN are involved in VNS-mediated regulation of hepatic production of proinflammatory cytokines. Methods: An animal model of hepatitis was generated by intraperitoneal injection of concanavalin A (ConA) into rats, and e… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…As shown above, both VNS can reduce brain tissue or serum TNF-α levels by stimulating the left or right vagus nerve for 10-20 min in animals with weight-drop brain injury. It is not completely clear how VNS inhibits neuroinflammation and reduces inflammatory factors, such as TNF-α, but studies have found that VNS can activate alpha7 nicotinic acetylcholine receptor (α7nAChR) on microglia to regulate NF-κB, JAK2/STAT3, PI3K/AKT signaling pathways to inhibit the expression of TNF-α, IL-1, IL-6, and other inflammatory factors (33,43,44). In addition, Vishal Bansal et al found that VNS can upregulate the expression of brain gut peptides, which can reduce the release of TNF (30).…”
Section: Neuroinflammationmentioning
confidence: 99%
“…As shown above, both VNS can reduce brain tissue or serum TNF-α levels by stimulating the left or right vagus nerve for 10-20 min in animals with weight-drop brain injury. It is not completely clear how VNS inhibits neuroinflammation and reduces inflammatory factors, such as TNF-α, but studies have found that VNS can activate alpha7 nicotinic acetylcholine receptor (α7nAChR) on microglia to regulate NF-κB, JAK2/STAT3, PI3K/AKT signaling pathways to inhibit the expression of TNF-α, IL-1, IL-6, and other inflammatory factors (33,43,44). In addition, Vishal Bansal et al found that VNS can upregulate the expression of brain gut peptides, which can reduce the release of TNF (30).…”
Section: Neuroinflammationmentioning
confidence: 99%